Konsep ‘Container Shelter’ Untuk Mendukung Program ‘Re Development’ Kampung Kumuh Di Pusat Kota - Syahyudes Rina (Institut Teknologi Sains Bandung, 2021)
A local government policy of Bandung City related to the re-building of slums area or kampung kumuh concept is the vertical row houses development. In practice, people are temporarily moved to a relocation site or to find houses for rent with a specific budget. Both of these options were complained about and rejected by people with various considerations that became problems in the row houses development. Based on this, it is concluded that there is a need for shelter as one of the temporary infrastructures provided for the initial step in the Re-Development program related to the people's sustainability lives. Related to the effectiveness of shelter development, containers can be used as houses materials. This trend is triggered by environmental problems, where containers that have been used piled up and do not return to their place due to shipping empty containers more expensive. Containers are modified to make housing units, with improved green housing value through container reused. The method of data and information were collected: a) field observations and interviews the settlement characteristics (physical and environmental, socio-economic, and residence); b) institutional surveys, c) secondary surveys covering theoretical studies and regulations. The method of analysis uses: a) qualitative method, by describing the data and information obtained, b) analyzing by literature review, comparing to policy and concept of ReDevelopment, container houses, and healthy house standards; c) functional design methods include analysis of users, activities, and space requirements; d) arrange the concept of a container shelter, then reflected into the function of macro space (site) and micro space (building). The output of this study is the housing container to refers the settlement characteristics, environmental requirements, modular methods, materials and container construction, unloading function of the house, according to needs people low income, and that the needs to maintains the preservation of the residential in the transition period.